A comparative histological study on the blood film of young and adult, male and female Monkeys (Chlorocebus pygerythrus): Muntadher S. Al-Zubaidi and Amer M. Hussin - Hussin, Amer M. (The Iraqi Journal of Veterinary Medicine, 2015)
Twenty Vervets monkeys were used to study the effect of sexes and ages on morphohistological and hematological pictures. The study revealed that age and sex affect blood values. Vervet monkeys registered a significant dominancy of hematological parameters in adult males. Erythrocytes of vervet monkeys were of macrocytic type, howell-Jolly bodies were observed. Rouleaux formation, Anisocytosis, Aggregation, and Agglutination were not observed. A significant predominancy of neutrophils in females and lymphocytes in males was recorded. The neutrophil was well defined, large with ring-shaped highly segmented nucleus. Band neutrophils were not observed in peripheral blood. Eosinophils recorded high values. Circulating leukocytes acted as a transient phase in the functional development of tissue leukocytes. Lymphocytes were the most common cells among leukocytes. Three sizes of lymphocytes and two of monocytes were registered. The value of monocytes percent was higher in males. The herein study declared that blood platelets showing different sizes, shapes and affinities for basic stains and according to these functional affinity, light resting and dark stimulating blood platelets were classified. There was a reverse relationship between the number of erythrocytes and blood platelets among different sexes and ages. In conclusion, the present study hypothesized that blood platelets serve as a supporting cells for blood cells especially erythrocytes. Besides, humoral immune defense in monkeys were well developed.